The Professions of Public Health - Fox, Daniel M. (© American Journal of Public Health 2001, 2001)
Law has been an essential tool of public health practice for centuries. From the 19th century until recent decades, however, most histories of public health described, approvingly, the progression of the field from marginally useful policy, made by persons learned in law, to effective policy, made by persons employing the methods of biomedical and behavioral science. Historians have recently begun to change this standard account by documenting the centrality of law in the development of public health practice. The revised history of public health offers additional justification for the program of public health law reform proposed in this issue of the Journal by Gostin and by Moulton and Matthews, who describe the new program in public health law of the Centers for Disease Control and Prevention.